Myricetin induces apoptosis and autophagy by inhibiting PI3K/Akt/mTOR signalling in human colon cancer cells - Ming-liang Zhu; Pei-min Zhang; Min Jiang; Shu-wen Yu; Lu Wang (BMC, 2020)
Abstract Background The compound 3,3',4',5,5',7-hexahydroxyflavone (myricetin) is a natural flavonoid with antitumour activity. Most of the studies on myricetin have focused on the induction of tumour cell apoptosis, and little is known about the regulatory effects of myricetin on autophagy in colorectal cancer. Methods Here, we studied the effects of myricetin on colon cancer cell proliferation, apoptosis and autophagy. We detected colon cancer cell apoptosis induced by myricetin via flow cytometry and Hoechst 33258 staining. Transmission electron microscopy was performed to observe the morphological changes associated with autophagy. The expression levels of apoptosis-, autophagy- and PI3K/Akt/mTOR signalling-related proteins were measured by Western blot analysis. Results This study confirmed that myricetin inhibits the proliferation of 4 kinds of colon cancer cell lines. Myricetin induced cell apoptosis and autophagy by inhibiting PI3K/Akt/mTOR signalling pathway. In addition, the inhibition of autophagy with 3-methyladenine (3-MA) promoted the apoptosis of myricetin-treated colon cancer cells. Conclusions Considering that myricetin induces apoptosis and autophagy in colon cancer cells, myricetin may become a viable candidate for chemotherapy; it could be used to exert tumour inhibitory effects alone or as adjuvant chemotherapy to inhibit autophagy. These studies may provide further evidence for the potential use of myricetin in the treatment of colon cancer.